Rat psychomotor development and apoptotic protein expression in their brains after glucocorticoid treatment - Petr N. Menshanov; Anita V. Bannova; Nikolay N. Dygalo (Syiah Kuala University, 2012)
A single injection of low-dose dexamethasone on postnatal day 3 resulted in the upregulation of key apoptotic enzyme – active caspase-3 in the rat cortex 120 hours after injection, and was followed by a delayed development of neonatal startle reflex and cliff avoidance reaction, an arrest of body weight gain and reduced spontaneous locomotor activity of pups. A single hydrocortisone administration to neonatal rats was only followed by a short-term delay in body weight gain, with no changes in the levels of active caspase-3 in the cortex and brainstem, as well as with no abnormalities in neurodevelopment. These results evidence for lesser neurotoxicity of natural hormone during neonatal development in comparison with dexamethasone and suggest the possibility that hydrocortisone might be used as a substitution for its synthetic analogue in the perinatal medicine